Wheat-Psathyrostachys huashanica 4Ns Additional Line Confers Resistance to Fusarium Head Blight - Yinghui Li; Hang Peng; Hao Zhang; Liangxi Li; Muhammad Saqlain; Dandan Wu; Wei Zhu; Lili Xu; Yiran Cheng; Yi Wang; Jian Zeng; Lina Sha; et al. (Plants)
Fusarium head blight (FHB) is one of the major wheat diseases caused by Fusarium species (mainly Fusarium graminearum and Fusarium asiaticum), resulting in significant global wheat yield losses and risks to food security. Breeding wheat varieties with resistance genes is the most environmentally friendly and economical strategy for controlling FHB. Psathyrostachys huashanica Keng ex P. C. Kuo (2n = 2x = 14, NsNs), which showed abiotic tolerance and biotic resistance, has significant research value and potential as an important genetic resource for wheat improvement. In previous studies, we crossed Psathyrostachys huashanica with common wheat and developed wheat lines containing different NS chromosomes. In this study, we identified a 4NS additional line, DA26, from the progenies of wheat-P. huashanica-derived lines using genomic in situ hybridization (GISH) and fluorescence in situ hybridization (FISH) analyses. Line DA26 showed high resistance to Fusarium head blight (FHB) in the greenhouse and field conditions. However, the parental common wheat lines Chinese Spring (CS) and CSph2b mutant showed high susceptibility to FHB. A field evaluation of the agronomic traits showed that the plant height of DA26 was significantly lower than CS, while there were no significant differences in the other agronomic traits. In addition, we also developed eight 4Ns-specific primers to identify the 4Ns chromosome, which can facilitate wheat breeding and FHB resistance gene mapping in the future.